2014
DOI: 10.1162/jocn_a_00497
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Dorsal/Ventral Stream Dynamics during Figure-ground Segregation

Abstract: The visual system has been commonly subdivided into two segregated visual processing streams: The dorsal pathway processes mainly spatial information, and the ventral pathway specializes in object perception. Recent findings, however, indicate that different forms of interaction (cross-talk) exist between the dorsal and the ventral stream. Here, we used TMS and concurrent EEG recordings to explore these interactions between the dorsal and ventral stream during figure-ground segregation. In two separate experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 56 publications
(102 reference statements)
2
11
0
Order By: Relevance
“…It has been demonstrated that a shift of attention to either the left or right visual hemifield decreases alpha oscillations in the contralateral hemisphere, while increasing them in the ipsilateral hemisphere (Worden et al, 2000;Sauseng et al, 2005;Thut et al, 2006). Furthermore, recent studies have shown that alpha power increases in the dorsal stream when a task relies on ventral stream processing (Jokisch and Jensen, 2007;Wokke et al, 2014). In the present study, we observed a smaller decrease of parietal alpha oscillation after presentation of a target cue when participants became sensitive to implicit cueing (Fig.…”
Section: Alpha Oscillations and Gatingsupporting
confidence: 62%
“…It has been demonstrated that a shift of attention to either the left or right visual hemifield decreases alpha oscillations in the contralateral hemisphere, while increasing them in the ipsilateral hemisphere (Worden et al, 2000;Sauseng et al, 2005;Thut et al, 2006). Furthermore, recent studies have shown that alpha power increases in the dorsal stream when a task relies on ventral stream processing (Jokisch and Jensen, 2007;Wokke et al, 2014). In the present study, we observed a smaller decrease of parietal alpha oscillation after presentation of a target cue when participants became sensitive to implicit cueing (Fig.…”
Section: Alpha Oscillations and Gatingsupporting
confidence: 62%
“…Although we have emphasized the unique role of dorsal cortex in representing 3-D shape, location, distance, and object motion, shape-selective regions within the ventral and dorsal pathways nevertheless seem to interact during shape perception (Galletti & Fattori, 2018; Janssen et al, 2018; Van Dromme et al, 2016; Wokke et al, 2014). A number of regions in dorsal cortex (such as AIP and CIP) share anatomical connections with object-selective areas in the ventral pathway (Borra et al, 2008; Liu et al, 2017; Premereur, Van Dromme, Romero, Vanduffel, & Janssen, 2015; van Polanen & Davare, 2015; Webster, Bachevalier, & Ungerleider, 1994; Yeatman et al, 2014).…”
Section: Discussionmentioning
confidence: 73%
“…In their view, this finding suggests a release of inhibitory connections between object-selective area LO and the scene processing pathway. More recently, Wokke, Scholte, and Lamme (2014) showed that LO TMS resulted in increased performance in motion-defined figure-ground segregation, supporting the existence of a ''push-pull'' mechanism in which dorsal and ventral extrastriate areas are activated or inhibited depending on stimulus and task characteristics. Accordingly, it is possible that interfering with LO in our clearness experiment favored the processing of features mainly mediated by the dorsal stream, such as luminance, spatial arrangement and implied dynamism of the image, leading to increased clearness of paintings in which these cues were more salient (i.e., abstract paintings lacking object content).…”
Section: Discussionmentioning
confidence: 88%